Commentary on the third Geneva Convention treatment of prisoners of war (Cambridge University Press, 2021)
The Third Geneva Convention remains the most comprehensive instrument for the protection of prisoners of war in international law today. Its purpose is to ensure that all such prisoners are treated humanely and held in decent conditions, regardless of which side they belong to. The ICRC produced its original Commentary on the Third Convention in 1960. Seventy years later, there is a need to look at the provisions of this fundamental treaty through the prism of new developments in law and practice. As with all international law, the Convention is a living instrument, and it must be interpreted and applied in light of contemporary circumstances. In view of the decreasing respect for the basic human values enshrined in international law, the updated Commentary on the Third Geneva Convention is timely. It crucially clarifies the status of prisoners of war and the treatment due to them, so that what these rules mean today is understood by all. The Convention aims to protect the physical and mental integrity of prisoners of war and to ensure that the detaining authorities provide for their physical and psychological needs. Under its provisions, murder, torture and any other form of inhumane or degrading treatment are prohibited. Prisoners of war must have access to food, health care and hygiene facilities, and it is mandatory to identify detained persons and to enable them to maintain contacts with the outside world so that they do not go missing.